ChemInform Abstract: Cobalt‐Catalyzed Decarboxylative 2‐Benzoylation of Oxazoles and Thiazoles with α‐Oxocarboxylic Acids. Issue 11 (February 2016) - Yang, Ke; Chen, Xinyong; Wang, Yuqi; Li, Wanqing; Kadi, Adnan A.; Fun, Hoong‐Kun; Sun, Hao; Zhang, Yan; Li, Guigen; Lu, Hongjian
Abstract: The title transformation represents the first example of Co‐catalyzed decarboxylative C—H functionalization and provides a complementary approach to important bioactive heteroaryl ketone derivatives, e.g. (III), (V), (VIII), and (X).